Mobile health van as an intervention to provide clinical support and health promotion to street children and marginalised populations in the National Capital Region of Delhi: a mixed-methods evaluation - Shanti Raman; Rajeev Seth; Yawar Qaiyum; Tanu Girotra Girotra; Id Mohammad; Indra Taneja (BMJ Paediatrics Open)
Background Urban health challenges, particularly for street and slum-dwelling children and families, have emerged as one of the most significant health concerns in India. While there is little published on effective healthcare delivery to these populations, mobile health vans (MHV) have been proposed as a proactive pathway to providing outreach healthcare. Our aims were to evaluate the impact of Bal Umang Drishya Sanstha (BUDS) MHV in providing health and support services to the urban slum populations in Delhi National Capital Region (NCR), focusing on benefits to children.Methods This was a mixed-methods evaluation, using routinely collected data. We collated and reviewed available data recorded by the BUDS staff in their health record system from June 2017 to December 2023. Qualitative data were provided by two recent focus group discussions carried out in the community; one with 18 mothers and another with a mixed group of 12 adults—all had used MHV clinics for children in their families. We chose two typical case studies that were reported to the funding bodies.Results Between 2017 and 2023, there were a total of 41 062 clinic visits for children<18 years, with visits increasing steadily and peaking at 8864 in 2023. Just under 10% of encounters were referred to specialist services, 122 children were diagnosed with disability. Health education sessions were provided mainly in group settings, to over 70 000 children. Themes extracted from focus group discussions were enhanced access to healthcare, quality of care, value adds from MHV and suggestions for improvement. Families expressed overwhelming appreciation of BUDS MHV. Case studies illustrated the benefits of facilitated access to tertiary healthcare.Conclusions MHV can serve as a valuable source of primary healthcare for street and slum-dwelling children and their families. Other benefits are empowering communities with health literacy and negotiating pathways to tertiary care.